2019
DOI: 10.2196/13301
|View full text |Cite
|
Sign up to set email alerts
|

Using Stakeholder Values to Promote Implementation of an Evidence-Based Mobile Health Intervention for Addiction Treatment in Primary Care Settings

Abstract: BackgroundMost evidence-based practices (EBPs) do not find their way into clinical use, including evidence-based mobile health (mHealth) technologies. The literature offers implementers little practical guidance for successfully integrating mHealth into health care systems.ObjectiveThe goal of this research was to describe a novel decision-framing model that gives implementers a method of eliciting the considerations of different stakeholder groups when they decide whether to implement an EBP.MethodsThe decisi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 19 publications
0
12
1
Order By: Relevance
“…Practitioners may also be concerned about what data are captured by the DMHI and whether the privacy and security of the DMHI aligns with regulations in their health care setting (Hermes, Burrone, et al, 2019). Thus, implementation strategies may include aligning practitioners on the advantages of implementing the DMHI (e.g., Quanbeck, 2019) and providing information about data security protections for the DMHI, such as by conducting local consensus discussions and educational meetings, as well as offering presentations about and demonstrations of the DMHI.…”
Section: Strategies For Dmhi Implementation In Health Care Settingsmentioning
confidence: 99%
“…Practitioners may also be concerned about what data are captured by the DMHI and whether the privacy and security of the DMHI aligns with regulations in their health care setting (Hermes, Burrone, et al, 2019). Thus, implementation strategies may include aligning practitioners on the advantages of implementing the DMHI (e.g., Quanbeck, 2019) and providing information about data security protections for the DMHI, such as by conducting local consensus discussions and educational meetings, as well as offering presentations about and demonstrations of the DMHI.…”
Section: Strategies For Dmhi Implementation In Health Care Settingsmentioning
confidence: 99%
“…is needed to consider the relevant costs and benefits associated with different courses of action, and whether and how EBI implementation and selected strategies will fit within their priorities and constraints. Stakeholder biases and preferences may affect the perceived usefulness of EBIs or implementation strategies [ 36 ]. For example, in a study about shared decision-making within cancer care, stakeholder interviews revealed widespread concerns about the likelihood of losing revenue as a substantial implementation barrier [ 6 ].…”
Section: Main Textmentioning
confidence: 99%
“…Zimmerman et al, for example, have leveraged the concept of bounded rationality as a foundation on which they have built comprehensive simulation models to aid healthcare stakeholders in providing treatment services for veterans with posttraumatic stress disorder [38]. These and other research efforts [12,39] aim to demonstrate the relevance and practical utility of behavioral economic concepts such as bounded rationality for implementation research and, in particular when considering the decision-making approaches and perspectives of different stakeholders.…”
Section: Limitationsmentioning
confidence: 99%
“…In particular, the societal perspective typically used for cost-effectiveness analysis in healthcare aggregates diverse stakeholder perspectives into a single, global perspective, but the accrual of value is often unevenly distributed across stakeholder groups. Each of these stakeholder groups, however, has different perspectives and different values on which they base economic decisions [12].…”
Section: Introductionmentioning
confidence: 99%